Effects of chronic hypoxia on the development and reproduction of the rat - Altland, Paul D. (1952)
In rats exposed daily for four hours at simulated altitudes of 25,000 feet, growth was slow, delayed puberty and life span was reduced by 50%. 25,000 feet daily, exposures produce severe testicle injury, which does not improve with acclimatization. The reproduction was completely inhibited in both sexes. At 18,000 feet playback occurs with low efficiency. The reduced litter size was associated with a decreased number of successful implantations and fetal resorption. Daily exposure of adult rats to 25,000 feet produced marked testicular damage after twelve exposures. Marked lesion was produced with few exhibitions (4) when done at weekly intervals. The time must be considered in the development of testicular injury after exposure to high altitudes. After the severe testicular damage occurred in rats was only possible to complete recovery of normal structure when all exposures ended. Exposure to ten day intervals prevents the slight recovery. After producing polycythemia in rats by short daily exposures, it was possible to maintain this status polycythemic exhibitions every two or three days; Longer idle periods produced the return of normal blood picture. The main pathological findings in rats exposed daily for prolonged periods, were the presence of 1) vegetations on the heart valves; 2) fibrous and fatty changes in left ventricular wall, 3) myocardial heart and kidney, occasionally ssociates with thrombus and embolism, and 4) hematuria and enterorrhagia.